Optimizing Qur'an Tahfiz Learning through Artificial Intelligence Training to Supporting the SDGs of Quality Education: Optimalisasi Pembelajaran Tahfiz Al-Qur’an melalui Pelatihan Artificial Intelligence dalam Mendukung SDGs Pendidikan Berkualitas - Muttakin, Fitriani; Monalisa, Siti; Abdilllah, Abdilllah; Amillia, Fitri; Mulyanto, Mulyanto (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
Tahfiz Al-Qur'an learning in nonformal institutions still faces obstacles in evaluating recitation and providing intensive memorization assistance. This community service activity aims to improve the understanding and skills of students and teachers in utilizing the Tarteel AI application as a supporting medium for tahfiz learning based on Artificial Intelligence (AI). The activity was carried out at PKBM Tahfiz Attamam Pekanbaru involving 95 participants consisting of students and teaching staff. The activity methods included socialization, training, hands-on practice, and evaluation using Likert scale-based pre-tests and post-tests. The evaluation results showed that 87% of participants understood the basic concepts of AI after the training, while 94% of participants demonstrated interest and readiness to utilize the Tarteel AI application as a supporting medium for tahfiz learning. In addition, teachers assessed that the application could help monitor students' memorization more systematically. This activity shows that the utilization of AI through the Tarteel AI application has the potential to support more adaptive tahfiz learning and contribute to the implementation of SDG 4 on Quality Education.